Understanding Toxoplasmosis in Reproductive-Age Women: Determinants of Infection and Evidence-Based Mitigation Approaches - Azka, Arlina; Soviadi, Nabila Vebiana; Saefurrohim, Muhamad Zakki; Azmiardi, Akhmad; Pakki, Irfansyah Baharuddin; Siswanto; Arfandi, Muh. Amri; Risva (Panakeia Journal of Epidemiology, 2025)
Toxoplasmosis remains a persistent public health concern among women of reproductive age due to the risk of congenital transmission and severe fetal outcomes. This narrative review aimed to synthesize recent evidence on infection determinants and evaluate evidence-based strategies to mitigate risks, addressing persistent gaps in awareness and intervention efficacy. A comprehensive literature search of PubMed and Google Scholar was conducted for studies published between 2016 and 2025. The findings reveal substantial geographic variation in seroprevalence, influenced by environmental conditions, cultural practices, and socioeconomic disparities. Higher infection rates were consistently reported among older, multiparous, rural, and less-educated women. Key risk factors included consumption of contaminated water, undercooked meat, and poor hygiene practices, while associations with cat ownership were inconsistent. Overall, knowledge and awareness of toxoplasmosis were low among women and healthcare providers. Although educational interventions and antenatal screening demonstrated potential benefits, their effectiveness remains insufficiently evaluated. Integrated, context-specific prevention strategies are urgently needed to reduce infection risk and prevent congenital toxoplasmosis.